Kesenjangan Implementasi Kurikulum Merdeka di Sekolah Dasar Daerah Terpencil Maluku: Analysis Fidelity of Implementation - Linda Violetta Siwalette; Zainal Arifin (Universitas Kristen Satya Wacana, 2026)
This study examines the level and gap of Merdeka Curriculum implementation in elementary schools located in remote areas of Maluku, Indonesia, using the Fidelity of Implementation (FOI) framework. A quantitative descriptive-comparative design with a cross-sectional survey was employed. The study involved 129 teachers selected through purposive sampling. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis involved descriptive statistics and gap analysis to identify discrepancies between ideal and actual implementation. The findings reveal that all dimensions of implementation are at a moderate level, with mean scores ranging from 3.26 to 3.44 (out of 5) and implementation gaps between 31.2% and 34.8%. The dimensions of quality of delivery and program differentiation demonstrate relatively higher performance, indicating teachers’ adaptive capacity in sustaining instructional quality and applying core curriculum principles. In contrast, adherence, dosage, and participant responsiveness show larger gaps, highlighting challenges in maintaining implementation consistency, instructional intensity, and student engagement. These results underscore that curriculum implementation in remote contexts is shaped not only by program design but also by contextual constraints, including limited resources, geographical isolation, and variations in student readiness. Future studies are recommended to employ mixed-method approaches and longitudinal designs to better capture the dynamics of curriculum implementation across different contexts.